Pelatihan Teknik Relaksasi untuk Menurunkan Kecemasan pada Primary Caregiver Penderita Kanker Payudara - Aprilya Dewi Kartika Sari; Subandi Subandi (Faculty of Psychology, Universitas Gadjah Mada, 2015)
This study was aimed to examine the effects of relaxation technique training to decrease anxiety level for family who care patient cancer at home. The participants of this study participated by five participants who had medium and high level of anxiety. Thedesign of the experiment was small N sample experiment, ABA design. The level of anxietywas measured quantitatively by adapted BAI scale. The treatment given to all participants was relaxation technique training. The training consisted of eight session, held for two weeks. The qualitative analysis was executed by analyzing of observation, interview, and homework. Statistic non parametric Wilcoxon and visual inspection graphics were used toanalyze the change of anxiety level before, during and after the training quantitavely There was significant score between base line and during training measurement, which Z=-0,023 and p=0,0215 (p<0,05), there was significant score between during training and follow upmeasurement, which Z=-0,023 and p=0,0215 (p<0,05) and there was significant score betweenbase line and follow up measurement, which Z=-2,041 and p=0,0205 (p<0,05). The result of this study showed that relaxation technique training was proven to be able to decrease anxiety level of each participants.